The Colonial Origins of Divergence in the Americas: A Labour Market Approach. - Allen, R; Murphy, T; Schneider, E (Department of Economics (University of Oxford), 2011)
Part of a long-run project to put together a systematic database of prices and wages for the American contingents, this paper takes a first look at standards of living in a series of North American and Latin American cities. From secondary sources we collected price data that - with diverse degrees of quality - covers various years between colonization and independence and, following the methodology now familiar in the literature, we built estimations of price indexes for Boston, Philadelphia, and the Chesapeake Bay region in North America and Bogota, Mexico, and Postosi in Latin America exploring alternative assumptions on the characteristics of the reference basket. We use these indexes to deflate the (relatively more scarce) figures on wages, and compare the results with each other, and with the now widely known series for various European and Asian cities. We find that real wages were higher in North America than in Latin America from the very early colonial period: four times the World Bank Poverty Line (WBPL) in North America while only two times the WBPL in Latin America. These wages place the North American colonies among the most advanced countries in the world alongside Northwestern European countries and the Latin American colonies among the least developed countries at a similar level to Southern European and Asian countries. These wage differences existed from the early colonial period because wages in the American colonies were determined by wages in the respective metropoles and by the Malthusian population dynamics of indigenous peoples. Settlers would not migrate unless they could maintain their standard of living, so wages in the colonies were set in the metrople. Political institutions, forced labour regimes, economic geography, disease environments and culture shaped the size of the economy of each colony but did not affect income levels.